Adaptive success index: A criterion for identifying most important species - Diogo S. B. Rocha; Leilton S. Damascena; Flávio França (African Journal of Environmental Economics and Management, 2022)
This article introduces the Adaptive Success Index (ASI) as a criterion for deciding which species are actually important in a given list of species either based on the Importance Value Index (IVI) or on the Cover Value Index (CVI).